The human side of seafaring - Chua, Wan Sing. (2013)
Past literature has portrayed seafaring as being unique and being one of the finest of lives. However, seafarers have, in recent years, displayed a lack in their professionalism. Thus, the lack of quality and motivated seafarers is of grave concern. To date, little research has been conducted on this aspect. As such, this study shall investigate the underlying reasons behind the lack of motivation and professionalism of seafarers. This paper will be divided into three segments. The first segment shall delve into past literature and interviews with ship managers and crew, which will shed light on the push and pull factors of a seafaring career. It is discovered that most tend to shun this career due to various reasons such as the increasing affluence of the economy, rising career expectations, as well as the negative reputation of the shipping industry. In contrast, a seafaring career is still attractive because of the relatively high pay, strong seafaring traditions, and the opportunity to seek adventure as well as to meet foreigners and new people. The second segment shall use the Maslow’s hierarchy of needs to make a comparison between the past and present conditions of seafaring. The comparison will assist in determining if changes in the environment were accountable for the lack of motivation in seafarers. From the data collected, it is observed that the conditions of seafaring have improved. Overly high expectations and lack of full understanding of the job scope of a seafarer’s life and career path of the seafarers were attributable to their lack of motivation to remain as seafarers in the medium to long term. In the third segment, practical recommendations will be suggested. This segment will be divided into 3 main categories: talent acquisition, talent management and talent retention. Talent acquisition shall detail the use of social media, greater gender diversity as well as corporate social responsibility to increase the number of recruits in the workforce. On the other hand, talent management shall outline the use of skills development. Lastly, talent retention shall involve the use of higher wages and better benefits such as higher connectivity as well as encouraging greater interaction between crew on board. Overall, this research aims to lay the foundation needed to deal with the self-actualising needs of seafarers.